2004
DOI: 10.1088/0953-8984/16/41/028
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline structure of SrAlF5investigated by vibrational spectroscopy

Abstract: SrAlF 5 has been considered as one of the rare fluoride ferroelectric crystals, belonging to the polar I 4 group. However, recent x-ray diffraction data suggest that the correct structure is centrosymmetric (I 4 1 /a). Since ferroelectricity is forbidden in this structure, the existence of an inversion centre was investigated by vibrational spectroscopy. Thus, measurements on SrAlF 5 single crystals have been made by polarized Raman scattering and infrared reflectance spectroscopy. The results, discussed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…Around the crystal melting point, the Raman peak at 550 cm −1 disappears, which is accompanied with three new Raman peaks appearing at 270, 490, and 600 cm −1 . The similar Raman peaks are observed in SrAlF 5 crystal, [25] of which three characteristic vibrational peaks are located at 290, 515, and 600 cm −1 . It is well known that in the SrAlF 5 crystal, the AlF 6 octahedron forms a chain structure by sharing the api-cal F − ions along the c axis, Sr 2+ ions are distributed in the fluoroaluminate frame.…”
Section: High-temperature Raman Spectrasupporting
confidence: 74%
“…Around the crystal melting point, the Raman peak at 550 cm −1 disappears, which is accompanied with three new Raman peaks appearing at 270, 490, and 600 cm −1 . The similar Raman peaks are observed in SrAlF 5 crystal, [25] of which three characteristic vibrational peaks are located at 290, 515, and 600 cm −1 . It is well known that in the SrAlF 5 crystal, the AlF 6 octahedron forms a chain structure by sharing the api-cal F − ions along the c axis, Sr 2+ ions are distributed in the fluoroaluminate frame.…”
Section: High-temperature Raman Spectrasupporting
confidence: 74%
“…Even though the polarization selection rules of the Raman spectra support a centrosymmetric space group, as it was pointed out by Silva et al [12], the number of observed vibrational bands is systematically one quarter of that predicted by the factor group analysis of the Kubel's crystalline structure (Figs. 1 and 2).…”
Section: Results and Discusionmentioning
confidence: 64%
“…In a recent work, we investigated the existence of an inversion center in SrAlF 5 using polarized Raman and infrared spectroscopies [12]. These results suggest a centrosymmetric crystalline system, but whose unit cell should be one quarter of the one proposed by Kubel.…”
Section: Results and Discusionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been shown that SAF is highly transparent down to the cutoff wavelength near 150 nm and its band gap was estimated to be 12 eV [1,2]. Vibrational spectroscopy studies of SAF were performed in [3]. However, the most interesting properties of this compound arise from its complex structure [4,5].…”
Section: Introductionmentioning
confidence: 99%